Comparison of laboratory and immune characteristics of the initial and second phase of tick-borne encephalitis. Issue 1 (31st December 2022) - Bogovič, Petra; Kastrin, Andrej; Lotrič-Furlan, Stanka; Ogrinc, Katarina; Avšič Županc, Tatjana; Korva, Miša; Knap, Nataša; Resman Rus, Katarina; Strle, Klemen; Strle, Franc
ABSTRACT: Tick-borne encephalitis (TBE) usually has a biphasic course which begins with unspecific febrile illness, followed by central nervous system involvement. Because TBE is not yet suspected during the initial phase, knowledge of early TBE pathogenesis is incomplete. Herein we evaluated laboratory and immune findings in the initial and second (meningoencephalitic) phase of TBE in 88 well-defined adult patients. Comparison of nine laboratory blood parameters in both phases of TBE revealed that laboratory abnormalities, consisting of low leukocyte and platelet counts and increased liver enzymes levels, were predominately associated with the initial phase of TBE and resolved thereafter. Assessment of 29 immune mediators in serum during the initial phase, and in serum and cerebrospinal fluid (CSF) during the second phase of TBE revealed highly distinct clustering patterns among the three groups. In the initial phase of TBE, the primary finding in serum was a rather heterogeneous immune response involving innate (CXCL11), B cell (CXCL13, BAFF), and T cell mediators (IL-27 and IL-4). During the second phase of TBE, growth factors associated with angiogenesis (GRO-α and VEGF-A) were the predominant characteristic in serum, whereas innate and Th1 mediators were the defining feature of immune responses in CSF. These findings imply that distinct immune processes play a role in the pathophysiology of different phases of TBE and in different compartments.